Manual Material Handling Training for Workers in The Furniture Industry - Kusuma, Early Widya; Anisa, Asriyani Fidia; Intanni, Restyantika Mahadewi; Widodo, Edwin; Santosa, Jessica Gabriella Budi (Universitas Negeri Semarang, 2023)
The work processes in the furniture industry starts from wood transportation, construction, sanding, assembling, and finishing. One of the potential hazards that always exist in every work process in the furniture industry is ergonomic hazards. The risks of Manual Material Handling (MMH) that includes lifting and lowering, pushing and pulling, rotating, carrying, and holding against an object adversely affect both the company and workers. This study aims to determine potential ergonomic hazards and control efforts to reduce risk of ergonomic hazards and injuries to furniture industry workers by providing training Occupational Safety and Health and proposed work system during Manual Material Handling activities. The method used to identify is the Hazard Identification Risk Assessment Control (HIRAC) technique. HIRAC used to help provide an understanding of the hazards that exist in each work process to minimize the occurrence of adverse Occupational Diseases. This research is qualitative research with observation and interview data collection techniques. Analysis techniques in this research included data reduction, data presentation, conclusions, and verification. Results of the evaluation showed that the identification of ergonomic hazards in the furniture industry was found in all furniture work processes from wood cutting to finishing.